PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN, INVESTMENT OPPURTUNITY SET TERHADAP VOLUNTARY - Nindhy Sellyna Pratiwi; Dirvi Surya Abbas; Imam Hidayat; Husna Darra Sarra (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the effect of profitability, liquidity, leverage and company size on voluntary disclosure. profitability is measured by return on equity (ROE), liquidity is measured by the current ratio (CR), Leverage is measured by the debt to equity ratio (DER), company size is measured by the natural logarithm of total assets. Voluntary disclosure as the dependent variable is measured by the disclosure index for the number of items disclosed by the company.This study used a sample of banking sector companies during the 2015-2019 period with a purposive sampling method. The data used are obtained from annual reports listed on the Indonesia Stock Exchange. There were 7 companies during the 2015-2019 period that met the criteria. The analysis method used is panel data regression analysis.The results of this study indicate that profitability has a significant effect on voluntary disclosure. Meanwhile, liquidity, leverage has no significant effect on voluntary disclosure, and company size has a significant effect on voluntary disclosure.